2019
DOI: 10.1002/ange.201901672
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Solid‐State Phosphorescence and Delayed Fluorescence at Room Temperature by a Twisted Hydrocarbon

Abstract: The dehydrating cyclotrimerization of 1-tetralone in the presence of titanium tetrachloride at high temperatures leads to homotruxene,anonplanar arene in whicht he twist angles between its three outer benzene rings and the central benzenea re stabilized by ethylene bridges.T his non-planar configuration allows for pronounced spin-orbit coupling and ah igh triplet energy,l eading to room-temperature phosphorescence in air with al ifetime of 0.38 sa nd aquantum yield of 5.6 %, clearly visible to the human eye af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 34 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Thus, more and more scientists have devoted themselves into the research of it in recent years. [82][83][84][85][86][87][88][89][90][91] Especially, Ruren Xu and coworkers proposed "Towards a new discipline of condensed matter chemistry" in 2018. [82,83] It is believed that after constant exploration, the molecular structure-packing property relationship could be revealed clearly and the adjustment of luminescence property in aggregation state could be easily realized from the source of molecular design.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Thus, more and more scientists have devoted themselves into the research of it in recent years. [82][83][84][85][86][87][88][89][90][91] Especially, Ruren Xu and coworkers proposed "Towards a new discipline of condensed matter chemistry" in 2018. [82,83] It is believed that after constant exploration, the molecular structure-packing property relationship could be revealed clearly and the adjustment of luminescence property in aggregation state could be easily realized from the source of molecular design.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Consequently, the delayed emission was assigned to TADF of SP1. 25,[58][59][60][61] After irradiating it with 365 nm light for about 1 s, the peak at 588 nm Page 8 of 24 CCS Chemistry This article presented here has been accepted for publication in CCS Chemistry and is posted at the © 2021 Chinese Chemical Society.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, the heavy atoms (eg., Br and I) ( Cai et al, 2018 ; Wang et al, 2021b ) and carbonyl groups ( Zhao et al, 2016 ; Jia et al, 2020 ) were incorporated into organic molecules to promote ISC process for achieving ultralong RTP, in combination with the suppression of the nonradiative quenching through rigid environment, ( Wu et al, 2020 ; Zheng et al, 2020 ; Zhou et al, 2020 ; Chen et al, 2021 ; Xie et al, 2021 ), such as crystal engineering and host-guest system. Very recently, Bechtold et al reported that the nonplanar aromatic hydrocarbon, named as 5,6,11,12,17,18-hexahydrobenzo [2,1-p]chrysene (HD), ( Salla et al, 2019 ), can show an ultralong RTP, which was attributed to the pronounced SOC induced by non-planar configuration. However, the enhanced SOC also reduces the RTP lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…The 5′-phenyl-1,1’:3′,1″-terphenyl (PT) has a faint RTP in crystal, while HD shows an efficient RTP with a lifetime of 380 m by introducing saturated ethylene bridges between the central benzene and outer benzene rings of PT. ( Li et al, 2015 ; Salla et al, 2019 ). Therefore, PT and HD molecules are good prototype to expound the dependence of ultralong RTP on the nonplanar conformation.…”
Section: Introductionmentioning
confidence: 99%